2019
DOI: 10.2139/ssrn.3395012
|View full text |Cite
|
Sign up to set email alerts
|

Attribute Sentiment Scoring with Online Text Reviews: Accounting for Language Structure and Attribute Self-Selection

Abstract: The authors address two novel and significant challenges in using online text reviews to obtain attribute level ratings. First, they introduce the problem of inferring attribute level sentiment from text data to the marketing literature and develop a deep learning model to address it. While extant bag of words based topic models are fairly good at attribute discovery based on frequency of word or phrase occurrences, associating sentiments to attributes requires exploiting the spatial and sequential structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…For example, Liu et al [48] analyzed consumer reviews and reported that aesthetics and price influence conversion. In addition, Chakraborty et al [49] developed a Hybrid CNN-LSTM model to extract emotional characteristics from text data, and showed that it solves difficult emotion classification problems well for Yelp reviews. Zhang et al [50] analyzed the effect of images on Airbnb's accommodation demand by using deep learning.…”
Section: Machine Learning Modelsmentioning
confidence: 99%
“…For example, Liu et al [48] analyzed consumer reviews and reported that aesthetics and price influence conversion. In addition, Chakraborty et al [49] developed a Hybrid CNN-LSTM model to extract emotional characteristics from text data, and showed that it solves difficult emotion classification problems well for Yelp reviews. Zhang et al [50] analyzed the effect of images on Airbnb's accommodation demand by using deep learning.…”
Section: Machine Learning Modelsmentioning
confidence: 99%
“…The surge of unstructured data sources has made methods for translating textual and visual content into useful information increasingly necessary. Online reviews have shown to be an incredibly rich source of unstructured information about consumer perceptions and experiences that provide a peek into the minds of its producers and receivers [3,4,5,6,7]. In this research, we sought to improve our understanding of the different modalities that constitute an online review -text and imagery.…”
Section: Discussionmentioning
confidence: 99%
“…It allows users to share their experiences with comments, reviews, pictures, ratings on a hotel, destination, or any tourist attraction. These reviews have been shown to be a valuable source of information [3,4,5,6,7] Future consumers resolve uncertainty about the quality of a hotel and its facilities by reading the online reviews given by customers on a website [1]. In addition, expectations of customers usually do not conform with their experience of a hotel because of varied reasons [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations